CIVIL SUBJECTIVITY OF YOUTH: FROM CONCEPTUAL ANALYSIS TO ASSESSING AND IMPROVING THE SITUATION - I. A. Simonova (Дискурс)
The article is devoted to social and philosophical analysis of civil subjectivity phenomenon. It focuses on forming and revising theoretical basis that encourages further operationalization of the concept of "civil subjectivity". The refined model of civil subjectivity, on which basis the conceptual field of research is systematized, is presented. The results of applying the proposed theoretical model are demonstrated. This model was employed in the course of empirical research (interview) conducted in August-October 2017 in Yekaterinburg. Based on the qualitative data received, major challenges of civil subjectivity of the respondents are described, and the main vectors of transformation in the field of work with youth are determined. The results show practical use of the concepts proposed.